Range extension of Amolops himalayanus (Boulenger, 1888) (Anura, Ranidae), first record from China and first description of the juvenile of this species - JiShan Wang; Shuo Liu; Hengying Wang; Mo Wang; Dingqi Rao (Biodiversity Data Journal)
Amolops himalayanus (Boulenger, 1888) is a poorly-known species which was originally described from north-eastern India over a hundred years ago. Currently, A. himalayanus is known only from India and Nepal and there is no reliable re-description or photos of this species reported.We record Amolops himalayanus (Boulenger, 1888) from China for the first time, based on one specimen collected from Yadong County, Xizang Autonomous Region, China. Although the specimen from China is a juvenile, however, phylogenetically, it was clustered with the syntype of A. himalayanus and the specimens of this species from Nepal with strong support and the genetic distance between the specimen from China and the syntype of A. himalayanus was only 0.7% in 16S gene sequences. We provide a description of the juvenile specimen and, in addition, we provide reliable photos of this species in life for the first time.